Rasa Memiliki Komunitas Nelayan Terhadap Instalasi TNI Angkatan Laut - Wijaya, Ahmad Burhan (Universitas Muhammadiyah Metro, 2023)
This study is aimed to describe the extent to which the sense of community of Paiton Fisherman under the nurture of the Indonesian Navy (TNI AL) toward the existence of TNI AL Installations. The well-being of the Fisherman community covers individuals and groups due to collective activities and Government development programs. This study uses a qualitative approach using semi-structured interviews with five people and 5 TNI AL military personnel in Pesisir-Sumberanyar village, Paiton-Probolinggo. The result: 1) membership, 2, influence, 3) sharing of emotional experience, 4) integrity and the fulfillment of needs (security, pride, and economy). A sense of community facilitates active participation and reinforces social capital toward community development. TNI AL institutions are suggested to encourage the Fisherman community to synergize for TNI AL activities. Selecting respondents with more variant backgrounds will enrich the research results for the following research.